(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Secondary research shows that consumer price knowledgeand gender has an effect on retail management strategy. Consumer knowledge andexpertise of industries prices, products and store location add to the ease atwhich consumers are able to cherry pick. Consumers are informed of discountedprices on products as well as the product assortment of a particular store,through marketing and store promotions. Cherry picking can be defined as takingthe best and leaving the rest and therefore cherry picking is used to portrayboth buyer and seller behaviour in retailing. Various sellers can be viewed asthose who are selective about which consumer profile they choose to target,whereas consumers are selective about which products or services they purchase.This article aims to establish the effect of consumer price knowledge andgender on retail management strategy. Consumers who are branded as cherrypickers are price sensitive shoppers with no brand loyalty but this market segment has been found to be sizable, heterogeneous, and potentially attractive for retailers, contrary to the myth that theyare a retailers’ nemesis. Price knowledge means the ability of buyers to keepprices in mind; it influences what, when, where and how much they buy. Cherrypickers build price competitions between retailers’; therefore they shouldstrive to have the most attractive offers and weekly advertisements, in orderto draw the cherry pickers in and obtaining a greater turnover